RESPONSE OF GROWING RABBITS (ORYCTOLAGUS CURNICULUS) FED DIETS CONTAINING RAW TALLOW (DETARIUM MICROCARPUM) SEED MEAL - Jiya, Elisha; Ijaiya, Abdumojeed, T; Alabi, Olusola J.; Makinde, John; Saidu, salamatu (Journal of Agricultural Sciences (Belgrade), 2018)
A 12-week study was conducted to determine the effect of graded levels of raw tallow seed meal (RTSM) on growth performance, blood biochemical profiles and organoleptic qualities of growing rabbits. Forty five (45) weaned rabbits between 5-6 weeks with average body weight of 500-600 g of mixed breed and sexes (female and male) were randomly allocated to five (5) treatment groups with nine (9) rabbits per treatment. There were three replicates with three rabbits per replicate. Raw tallow seed meal was included in the diet as a source of protein at graded levels of 0, 25, 50, 75 and 100 % to substitute Palm kernel cake (PKC). Results showed that RTSM significantly (p<0.05) influenced daily weight gain, daily feed intake and FCR of the rabbits. Rabbits fed T2 and T3 diets consumed feed and gained weight similar (p>0.05) to rabbits fed control diet. FCR was significantly better among rabbits fed the T1, T2 and T3 diets. All the blood parameters except red blood cell, MCH, MCHC, monocyte, globulin and glucose were significantly (p>0.05) influenced by the different dietary treatments. The results of organoleptic qualities revealed that tenderness, flavor, color and overall acceptability were not significantly (p>0.05) different. The juiciness of the rabbit meat was however differed (p<0.05) significantly. It was concluded that 50 % RSTM can be included in rabbit’s diet without adverse effect on growth performance and blood indices of rabbits.